Are American children and youth really such physically active as illustrated by ActiGraph data in national youth fitness survey? - Xiong Qin; Weimo Zhu; Xiaotian Gao; Huaijin Xu; Zezhao Chen (Heliyon)
Introduction: Physical activity (PA) brings health benefits to children and youth. As a result, PA guidelines for Americans suggested a minimum of 60 min moderate to vigorous PA (MVPA) everyday for children and youth. Surveys using questionnaires have been conducted but no studies used accelerometer to examine the PA participation of U.S. Children. The purpose of this study was to determine the PA participation using accelerometer data from the 2012 National Youth Fitness Survey. Methods: The PA monitor data, released in terms of MIMS, of each minute of each participant recruited in NNYFS aged from 6 to 15, were equated into ActiGraph Count and then compared with cutoff scores to determine the PA intensity. The accumulation of moderate to vigorous minute represents a person's daily MVPA time. The daily MVPA time per person was summarized, determined and compared by age, sex, race and BMI category. Results: Almost every participant have daily MVPA more than 60 min as recommended by the guideline. As age increase from 6 to 15, MVPA time decreases, and no differences of MVPA time were observed between normal weight groups and overweight/obese groups, different sex and race groups. Extremely long daily MVPA time was observed. Conclusion: Almost all the children and youth met the 60-min MVPA guideline and have very long MVPA time. The result is against the questionnaire results. The reason of extremely high MVPA time might due to that the data were collected at participants’ wrist and the algorithm of MIMS allowing plenty of noise been counted as PA. The future studies need to develop better algorithms dealing with wrist-worn data and noise filtering.